Impact of COVID-19 on Labor Market Outcomes of Refugees and Nationals in Kenya - Vintar, Mirko; Beltramo, Theresa Parrish; Delius, Antonia Johanna Sophie; Egger, Dennis Timo; Pape, Utz Johann (Washington, DC: World Bank, 2022)
This paper investigates the labor market outcomes for refugee and urban national communities in Kenya during the COVID-19 pandemic, using five waves of a novel high-frequency phone survey collected between May 2020 and June 2021. Even after conditioning on age, gender, educational attainment, and area of living, only 32 percent of refugees were employed in February 2020 compared with 63 percent of nationals. With the onset of the pandemic in March 2020, the share of employed for both refugees and nationals fell by around 36 percent, such that in May-June 2020, only 21 percent of refugees were still employed compared with 40 percent of nationals. Using a panel setup with wave and location fixed effects, the analysis finds that the recovery in the share of employed, hours worked, and household incomes was slower and often stagnant for refugees compared with the recovery of nationals. These differences cannot be explained by demographic factors, living in an urban or camp environment, having been employed previously, or sectoral choice, suggesting that a third, unobservable “refugee factor” inhibits refugees’ recovery after a major shock and aggravates preexisting vulnerabilities.